2009
DOI: 10.1158/0008-5472.can-09-1205
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Adhesion Protein-1 Enhances Tumor Growth by Supporting Recruitment of Gr-1+CD11b+ Myeloid Cells into Tumors

Abstract: Cancer growth is regulated by several nonmalignant cell types, such as leukocytes and endothelial cells, which reside in the stroma of the tumor. Vascular adhesion protein-1 (VAP-1) is an amine oxidase enzyme that is expressed on the surface of endothelial cells. It supports leukocyte traffic into inflamed tissues, but nothing is known about its possible role in cancer biology in vivo. Here, we report that B16 melanoma and EL-4 lymphoma remain smaller in VAP-1-deficient mice than in wild-type controls. We foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 44 publications
5
53
0
Order By: Relevance
“…This finding supports previous reports revealing the key role of VAP-1 in angiogenesis-related diseases, including cancer 13 and age-related macular degeneration. 5 To date, molecular diagnosis has not been introduced to patient care and need is great for in vivo molecular markers of angiogenic disease.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding supports previous reports revealing the key role of VAP-1 in angiogenesis-related diseases, including cancer 13 and age-related macular degeneration. 5 To date, molecular diagnosis has not been introduced to patient care and need is great for in vivo molecular markers of angiogenic disease.…”
Section: Discussionsupporting
confidence: 93%
“…A recent article also showed impaired leukocyte infiltration in cancer in VAP-1-deficient mice. 13 Tumor lymphangiogenesis in VAP-1Ϫ/Ϫ mice does not differ from wild type. 13 During tumor development and metastasis, cytokines such as VEGF-A and IL-1␤ are up-regulated.…”
Section: Vap-1 In Lymph-and Angiogenesis 1919mentioning
confidence: 98%
See 2 more Smart Citations
“…We have found that tumor progression is retarded in VAP-1-deficient mice (22). In this study, we therefore evaluated the effects of anti-VAP-1 Abs and SSAO inhibitors on leukocyte recruitment into tumors and tumor progression.…”
mentioning
confidence: 99%